Assortative mixing in eastern spadefoot (Scaphiopus holbrookii) spatial networks is driven by landscape features - Anne Devan‐Song; M. A. Walden; James R. Watson; Anna E. Jolles; Justine M. Fox; Nancy E. Karraker (Ecosphere, 2022)
Abstract Biotic and abiotic factors drive assortative mixing (preference for or sorting with individuals with similar characteristics) in animal populations on a landscape, with implications for dispersal, population structuring, and other ecological and evolutionary processes. However, patterns and generative mechanisms of assortative mixing are overlooked in amphibians outside of specific life history events such as reproduction. The aims of this project were to determine whether there is assortative mixing by size and life history category in eastern spadefoots (Scaphiopus holbrookii), whether these patterns are preserved across time and spatial scale, and quantify the nature and relative role of various habitat and soil features in explaining observed patterns in spatial organization of individuals. We conducted field surveys in southeastern Virginia, USA, in 2016 and 2017 during nonbreeding periods to create spatial networks of S. holbrookii. We quantified spatial assortativity by size and life history stage and evaluated the roles of multiple landscape features in explaining spatial organization of S. holbrookii. We found that S. holbrookii sorted spatially by size and sex outside of breeding periods, with juveniles and adults less likely to sort with each other. Within each life history stage, S. holbrookii sorted by size. These patterns were similar across time and spatial scale. Soil and habitat types had no effect on assortativity. Instead, the distance to nearest breeding pool, wetland, and meadow were related to life history stage assortativity, as well as size assortativity in males and subadults. Adult males and females displayed affinity for breeding pools and meadows and avoidance of other types of wetlands, while subadults and nonbreeding adults showed opposite patterns compared with breeding adults. Our results indicate that (1) previously established guidelines for the minimum size of buffer zones to protect wetland‐breeding amphibians may be inadequate, (2) nonbreeding wetlands may be important core habitat for subadults, and (3) the upland spatial organization of amphibians may be used to predict locations of undetected breeding pools.